Towards an international code of conduct for private security providers : a view from inside a multistakeholder process - Buzatu, Anne-Marie (SSR paper (Geneva Centre for the Democratic Control of Armed Forces), 2018)
"The use of private security companies (PSCs) to perform services that are traditionally associated with the state presents a challenge to regulatory and oversight frameworks. Analyzing developments leading to the International Code of Conduct for Security Providers (ICOC) and the ICOC Association, this paper argues that a multistakeholder approach to develop standards adapted for the private sector and which creates governance and oversight mechanisms fills some of the governance gaps found in traditional regulatory approaches."--